PENGARUH UKURAN PERUSAHAAN, RETURN ON ASSET, LEVERAGE, CAPITAL INTENSITY DAN INVENTORY INTENSITY TERHADAP TARIF PAJAK EFEKTIF (Studi pada Perusahaan Perdagangan yang Terdaftar di Bursa Efek Indonesia) - Tobing, Hendro; Andreas, Andreas; Volta Diyanto, Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research is to test and analyze the effect between company size, return on asset, leverage, capital intensity and inventory intensity on effective tax rate.The population in this study is trading companies listed in Indonesia Stock Exchange at 2014 - 2016. Sampling was done by purposive sampling method. Based on purposive sampling method, sampling obtained by 69 companies. The data was analysed by using multiple regression analysis with SPSS version 22.0. Based on the result of test in this research, the partial regression test (t test) indicate that company size, return on asset and leverage effect on effective tax rate. While capital intensity and inventory intensity has no effect on effective tax rate. Based on total adjusted R-square result proved that variables of company size, return on asset, leverage, capital intensity, and inventory intensity on effective tax rate results of 24,5% while the rest of 75,5% were affected by other variables that were not performed in this study.Keyword : Company Size, Return On Asset, Leverage, Capital Intensity, Inventory Intensity and Effective Tax Rate.